The profitability estimation of a 100 MW power-to-gas plant - Miao, Bin (2019)
Power-to-Gas (PtG) is a grid-scale energy storage technology that converts electricity into the gas fuel as an energy carrier. Specifically, it utilizes surplus renewable electricity to generate hydrogen from electrolysis with Solid Oxide Cell (SOC), and the hydrogen is then combined with CO2 through Sabatier process to form methane. The methane can be transported within existing natural gas pipeline or city gas pipeline for civil and commercial usages. To increase the utilization rate of the plant, it is sensible to make use of the reverse function of SOC, which is a Solid Oxide Fuel Cell (SOFC), to generate electricity when the grid is short of power. The energy input of this process is methane, and it is called Gas-to-Power (GtP). This study estimated the realistic cost of building a 100 MW PtG plant. The focus of this study is given to the effect of several parameters on the Levelized Cost of Electricity (LCOE) of the PtG plant.